FORMULATION AND CHARACTERIZATION OF 50% ETHANOL EXTRACT OF ARECA NUT (Areca catechu) NANOPARTICLES USING THE IONIC GELATION METHOD - Humaryanto; Fathnur Sani Sani K; Yuliawati; Ave Olivia Rahman; Muhaimin; Alfi Khatib (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
The extract of areca nuts (Areca catechu) contains secondary metabolites, such as flavonoids, alkaloids, saponins, tannins, and steroids. These compounds possess pharmacological effects and can be developed into herbal medicine products. The objective of this study is to determine the optimal nanoparticle formulation by varying the concentrations of chitosan and sodium tripolyphosphate. The 50% ethanol extract of areca nuts was obtained through the maceration method. The extract obtained calculation the yield value. Then tested for phytochemical screening. Subsequently, the extract was formulated into nanoparticle colloids with different ratios of extract concentration: chitosan: sodium tripolyphosphate: Tween 80. The resulting nanoparticles were characterized by their particle size, zeta potential, and polydispersity index. The research findings demonstrated that Formula 3 exhibited the best results, with a particle size of 254.2 ± 0,00, zeta potential of 12.7 ± 0,71, and polydispersity index of 0.436 ± 0,03. Keywords: Formulation, Nanoparticles, 50% Ethanol, Areca Nuts, Ionic Gelation.